Fish-derived bioactive peptide: Bioactivity potency, structural characteristics, and conventional and bioinformatics approaches for identification - Muhammad Alfid Kurnianto; Ifwarisan Defri; Fathma Syahbanu; Salma Shafrina Aulia (Future Foods, 2024)
Fish is a nutritious food that has been linked to human health, with bioactive peptides (BPs) playing an important role in this. Fish-derived BPs possess various functional properties, including antioxidant, antihypertensive, anti-diabetic, and antimicrobial activities. The mechanisms underlying these functional properties depend on the structural characteristics, such as amino acid composition, terminal amino acid type, hydrophobicity, molecular weight, and net charge of the BPs. To date, the production and identification of fish-derived BPs has been based primarily on conventional approaches. However, these methods are characterized by lengthy and time-consuming steps making BPs application expensive. To address these limitations, bioinformatics approaches based on biological data and computational modeling are emerging as a promising way to improve efficiency and reduce costs in the discovery and development of BPs. In recent years, several reports have demonstrated that bioinformatics approaches, either singular or in combination, can more rapidly and efficiently identify potential bioactivities, characteristics, and sequences of new fish-derived BPs. Quantitative structure-activity relationship and molecular docking studies provide basic structural information on the active site and reveal the mechanism underlying of BPs bioactivity. In light of the above discussion, this review discusses current research on the potential bioactivity of fish-derived BPs, structural characteristics, and methods of BPs production and identification, including both conventional and bioinformatics-driven approaches. This review highlights the role of bioinformatics in the identification of fish-derived BPs, using techniques such as database and proteolytic simulation, molecular docking and molecular dynamics. In addition, the review addresses existing challenges and outlines future perspectives for the use of fish-derived BPs and their bioinformatic analysis in advancing biomedical research.